VICARIOUS LIABILITY AND THE EVOLVING MASTER-SERVANT RELATIONSHIP IN THE GIG ECONOMY: A TORT LAW PERSPECTIVE (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The “Master-Servant Relationship in Torts: Liability, Duties, and Contemporary Challenges” is a nuanced exploration of the legal dynamics that govern the relationship between employers (masters) and their employees (servants) within the realm of tort law. This abstract provides a succinct overview of the topic, highlighting its significance, key principles, and contemporary challenges. This study acknowledges the critical role of vicarious liability, wherein employers can be held liable for the wrongful acts or omissions of their employees during the course of employment. It explores the nuanced criteria that determine the scope of employment, shedding light on when an employee’s actions are deemed to be within the purview of their employment. Furthermore, this abstract highlights contemporary challenges in the master-servant relationship. These challenges encompass the gig economy, where the traditional employer-employee model is blurred, the advent of remote work, which complicates the assessment of work-related acts, and the ever-evolving landscape of employment relationships in the digital age.